Toxicidade dos óleos essenciais sobre Thaumastocoris peregrinus, Cleruchoides noackae e na indução de resistência em Eucalyptus benthamii - Stenger, Luma Dalmolin (2017)
Eucalyptus plantations in Brazil have been attacked by exotic insects, causing significant losses in this crop. Thaumastocoris peregrinus feeds on the sap of the eucalypt leaves, which promotes a reduction in the photosynthetic rate, defoliation and, in some cases, the death of the plant. However, alternative control methods are being studied to reduce and/or eliminate the problems associated with this insect and the use of synthetic phytosanitary products. The objective of this work was to evaluate the toxicity of the essential oils of Melaleuca alternifolia, Casearia sylvestris and Eugenia uniflora on T. peregrinus, the selectivity of E.uniflora to the parasitoid eggs of Cleruchoides noackae and the potential of these oils as inducers of defense mechanism in Eucalyptus benthamii. For this purpose, the mortality of T. peregrinus was evaluated after contact with the essential oils (1,0%), and the oil of E. uniflora was selected to be evaluated in different concentrations on adults, 3° instar nymphs And eggs of T. peregrinus, and on the parasitoid of C. noackae eggs. The selectivity on this parasitoid was analyzed in pre-parasitism, post-parasitism (1 day) and post-parasitism (7 days). Evaluating the percentage of eggs parasitized by C. noackae, percentage of C. noackae emerged, sexual ratio of C. noackae and percentage of T. peregrinus nymphs hatched. The essential oils were analyzed by gas chromatography. The resistance induction test had the objective of evaluating the same essential oils as inducers of defense mechanisms in E.benthamii. Two bioassays were performed, 1) the essential oils were pulverized and after 30 days the biochemical analyzes of the foliar tissues were performed, evaluating total sugars, proteins, peroxidases, phenylalanine ammonia-lyase (FAL) and phenols. 2) seven days after the first analysis the essential oils were again sprayed and after 3 days the parameters mentioned above were evaluated. In the toxicity test, mortality of T. peregrinus (100%), after contact with E. uniflora essential oil (1,0%) was verified, and at 0,75% concentration showed insecticidal potential on adults, 3° instar nymphs and T. peregrinus eggs. This oil was selective to C. noackae when applied after parasitism (1 day). When applied pre-parasitism and post-parasitism (7 days) affected the biological parameters of this parasitoid. The major compounds found in the essential oil of M. alternifolia were, 1,8-cineol (72.31%) a-terpineol (8.55%), in C. sylvestris were g-murolene (19.55%), (15.24%) and s-amorphene (13.17%) and in E. uniflora calamen-10-one (20.20%), silfiperferol-6-em-5-one (10.06%), , Germacrona (6.61%). The essential oils of M. alternifolia, C. sylvestris and E. uniflora did not promote a significant increase in the levels of total sugars, proteins, peroxidase, FAL and phenols when analyzed within 30 days after spraying. The same oils sprayed and analyzed after three days have potential as inducers of defense mechanisms in E. benthamii seedlings.